The effect of FinTech development on bank risktaking: Evidence from Kenya - Rogers Ondiba Ochenge (Kenya Bankers Association (KBA), 2023)
Cognizant of the recent revolution in financial technology (FinTech), this paper explores the effect of FinTech development on bank risk-taking behavior in Kenya over the period 2008 to 2021. The study first develops a FinTech index using text mining technology and then relates this index to bank-risk taking in a dynamic panel regression model. The study uncovers the following empirical results: (i) The impact of FinTech on bank's risktaking shows a "U" shape, first falling bank risk and then rising. That is, at early stage of development, FinTech reduces risk-taking, but as key technologies mature and FinTech companies directly compete with traditional commercial banks, FinTech exacerbates risktaking. (ii) The impact of FinTech is heterogeneous across bank sizes. Specifically, large banks appear to be more sensitive to changes in FinTech development compared to small and medium-sized banks.
Keywords: 330